2011
DOI: 10.1002/app.34982
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and morphology of polypropylene‐calcium carbonate nanocomposites prepared by dynamic packing injection molding

Abstract: In this article, dynamic packing injection molding (DPIM) technology was used to prepare injection samples of Polypropylene-Calcium Carbonate (PP/CaCO 3 ) nanocomposites. Through DPIM, the mechanical properties of PP/nano-CaCO 3 samples were improved significantly. Compared with conventional injection molding (CIM), the enhancement of the tensile strength and impact strength of the samples molded by DPIM was 39 and 144%, respectively. In addition, the tensile strength and impact strength of the PP/nano-CaCO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The overall percentage of CaCO 3 in the nanocomposite was estimated to be 57.3 wt%; that is, the CaCO 3 content was high. Producing nanocomposites containing large amounts of inorganic materials is difficult via conventional mixing processes [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall percentage of CaCO 3 in the nanocomposite was estimated to be 57.3 wt%; that is, the CaCO 3 content was high. Producing nanocomposites containing large amounts of inorganic materials is difficult via conventional mixing processes [14].…”
Section: Resultsmentioning
confidence: 99%
“…The TGA result showed that the content of CaCO 3 in the whole sample was relatively high. Even though CaCO 3 nanocomposites have previously been synthesized [14,19,20], synthesizing nanocomposites with a high CaCO 3 content remains challenging. For example, in a previous synthesis of CaCO 3 nanocomposites, CaCO 3 particles with dimensions of several tens of nanometers, synthesized in advance, were mixed with polymers, but when high concentrations of these CaCO 3 particles were mixed with the polymers, CaCO 3 aggregated [21].…”
mentioning
confidence: 99%
“…e overall percentages of CaCO 3 in the composites were estimated to be 93.0, 93.2, and 93.5 wt.% for discs fabricated from the CaCO 3 -chitosan composites prepared at 4 and 95°C and the scallop shell disc, respectively; that is, the CaCO 3 contents were high. is is noteworthy because producing nanocomposites containing large amounts of inorganic materials is difficult via conventional mixing processes [13].…”
Section: Tgamentioning
confidence: 99%
“…In addition to an enhanced degree of orientation, Yang et al also observed well‐defined nanohybrid shish–kebab entities, in which CNTs acted as shish while HDPE lamellae acted as kebab, within the oriented zone of HDPE/CNTs composites prepared by OPIM. Gao et al prepared PP/CaCO 3 (9 wt%) nanocomposites utilizing OPIM technology and investigated the effect of oscillation pressure on the mechanical properties of PP/CaCO 3 and PP samples. The improvement of mechanical performances is shown in Table .…”
Section: Shear Controlled Orientation In Injection Moldingmentioning
confidence: 99%